The Effect of Bio Energy Power Exercise on Activities of Daily Living in Stroke Patients at Yastroki Yogyakarta - Renafa Septi Anggraini; Veni Fatmawati; Wika Yuniarwati (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2025)
Background: Stroke is a clinical manifestation of sudden focal or global brain dysfunction that lasts more than 24 hours or can result in death without any vascular abnormalities. It is the third leading cause of death after heart disease and cancer. According to the World Stroke Organization (2022), over 12.2 million people—or one in four individuals over 25 years old—may experience a stroke, with more than 101 million people currently living with the condition. Data from the Indonesian Health Survey reports a stroke prevalence of 8.3 per thousand. And one of them causes a decrease in daily living activities. Purpose: This study aims to examine the effect of Bio Energy Power Exercise on the activities of daily living (ADL) in stroke patients at Yastroki Yogyakarta. Method:  The research design uses methods using a quasi-experimental design with a pretest-posttest one-group approach. The sample consisted of 16 participants who met the inclusion criteria. Data were collected using the Katz Index questionnaire, administered before and after the intervention. The intervention involved Bio Energy Power Exercise performed twice a week for four weeks, with each session lasting 20 to 30 minutes.  Result: The results of the test using the Wilcoxon signed-rank test showed that p<0.05 (p=0.000), this shows that there is a significant influence of bio energy power gymnastics on daily living activities in stroke patients. Conclusion:  Bio Energy Power Exercise has a significant positive effect on the activities of daily living in stroke patients, highlighting its potential as a beneficial rehabilitation intervention.